Management and Evaluation of Vocational Training Programs at the Ponorogo Regency Vocational Training Center (VTC) - Alaska, Martha; Nurhadi, Didik; Romadin, Achmad (invotek, 2023)
The issue of employment and a decent living is crucial. This is complicated by developing an increasingly global world with increasingly fierce competition. Training is a factor in the development of Human Resources (HR). The success of an activity program depends on the management and evaluation results of the training program. This research aims to analyze the management and evaluation of the Ponorogo Regency Vocational Training Center. This research was a descriptive study with a qualitative approach using observation, interviews, and documentation. The information is obtained first, then used sources and techniques to triangulate it before being presented for discussion. The results of this study stated that training management at the Vocational Training Center (VTC) includes: the training process at the Vocational Training Center (VTC) covers planning, organization, implementation, and evaluation. The evaluation results show that the training met all requirements and needs (antecedents phase), was effectively implemented (transaction phase), and produced good average test results for trainees (outcomes phase). This indicates the VTC's commitment to providing quality training with successful outcomes.